DICEPHALUS TETRAPUS TETRABRACHIUS MONSTER AS A CAUSE OF DYSTOCIA IN CROSSBRED COW - KASRIJA, RAJESH; SINGH, PRAHLAD; VERMA, H K (The Indian Journal of Animal Reproduction, 2023)
A 6 year old crossbred cow with normal gestation and prolonged labour pain when examined per vaginum revealed two fetal heads and four legs in birth canal causing dystocia. Fetotomy was resorted to deliver the calf. The anatomical structure of the monster is described and discussed.
Keywords: Cow; Dystocia; Dicephalus; Tetrapus; Tetrabrachius